Students’ Motivation in EFL Learning - AlMunawwarah, Sophia Fithri (TELL - US JOURNAL, 2018)
This study explores types of motivation for students’ EFL learning and identifies factors that motivate them in the learning process. This is a descriptive study utilizing both quantitative and qualitative design by involving a class of one vocational school. Through close-ended questionnaire, open-ended questionnaire, and interview, the data were collected. The results of this study were in line with the previous findings (see Tamimi & Shuib, 2009; Yu, 2010; Tahaineh & Daana, 2013). The findings discovered that both instrumental and integrative motivation play a crucial role in the students’ EFL learning process within this context. Nevertheless, it revealed that the instrumental motivation had a predominant role in the EFL learning. Besides, the data showed that there were thirteen factors which affected the students in the learning as classified by Williams and Burden (1997, cited in Dornyei, 2001). However, since types of motivation and motivational factors are dependent upon context, it is suggested to conduct the research related to this topic in different context or site.